Effect of compatibilizer and organoclay content on structure, thermal, and mechanical properties of poly(butylene succinate)/(Ethylene acrylic acid)/Organoclay nanocomposites. Issue 3 (1st July 2015) - Tian, Qin; Qin, Shuhao; Zhou, Rong; Zhou, Rongfeng; Jiang, Yehua; He, Wentao; Xu, Guomin
Abstract : Poly(butylene succinate) (PBS)/(ethylene acrylic acid) (EAA)/organoclay nanocomposites were prepared by using the melt intercalation technique. EAA was used as compatibilizer and organoclay was used as inorganic filler. X‐ray diffraction and transmission electron microscopy results indicated the addition of compatibilizer led to a large increase in basal spacing of nanocomposites and better overall dispersion of organoclay in the PBS matrix. However, the basal spacing was found to be invariant as the organoclay content increased. The differential scanning calorimetry analyses revealed that the incorporation of the organoclay and EAA and the variation of organoclay content altered the melting behavior and crystallization properties of PBS. Storage and loss modulus of virgin matrix increased with the incorporation of organoclay and EAA, and a maximum for the nanocomposite with 9 wt% organoclay. Moreover, the glass transition temperatures also increased for the various organoclay‐containing samples. Mechanical properties showed an increase with the incorporation of organoclay and EAA. The 5 wt% organoclay‐filled PBS gave the highest tensile strength and notched Izod impact strength among all the composites. Further increments in organoclay loading reduced the tensile strength and notched impact strength of nanocomposites, which was thought to be the result of agglomeration. However, increments in clay loading enhanced the flexural strength and flexural modulus of nanocomposites, with a maximum at 9 wt% organoclay. J. VINYL ADDIT. TECHNOL., 23:219–227, 2017. © 2015 Society of Plastics Engineers